2012
DOI: 10.1002/pbc.24402
|View full text |Cite
|
Sign up to set email alerts
|

Assembly of a cohort of children treated for acute myeloid leukemia at free‐standing children's hospitals in the United States using an administrative database

Abstract: Pediatric Health Information System data were used to establish a multi-center cohort of 1,686 children treated for newly diagnosed acute myeloid leukemia (AML). The cohort assembly process, which included myeloid leukemia ICD-9 discharge diagnosis codes and manual review of induction chemotherapy, was validated by chart review at a single institution. The use of ICD-9 codes alone resulted in a poor positive predictive value (PPV; 31%). Inclusion of the results from the chemotherapy review improved the PPV to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
54
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
8

Relationship

7
1

Authors

Journals

citations
Cited by 34 publications
(54 citation statements)
references
References 14 publications
0
54
0
Order By: Relevance
“…Despite the strengths of PHIS data and the use of chemotherapy billing data in cohort establishment (28), this study has limitations. The definition if ICU care was based on resource utilization codes rather than physical patient location.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the strengths of PHIS data and the use of chemotherapy billing data in cohort establishment (28), this study has limitations. The definition if ICU care was based on resource utilization codes rather than physical patient location.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, the billing data for chemotherapy agents commonly used for the treatment of AML were manually reviewed for each remaining patient. Those patients who did not receive a chemotherapy regimen consistent with AML induction therapy were excluded (28). Patients entered the cohort on the day of their first hospitalization containing induction chemotherapy for AML (index admission).…”
Section: Methodsmentioning
confidence: 99%
“…14,15 The hospitals included in this study were primarily urban, academic hospital centers affiliated with major medical centers. The PHIS hospital size varies from 100 to 500 beds.…”
Section: Methodsmentioning
confidence: 99%
“…Patients with ALL or AML were identified with a combination of International Classification of Diseases, Ninth Revision , diagnosis codes and a manual review of induction chemotherapy exposures, as previously validated. 14,15 …”
Section: Methodsmentioning
confidence: 99%
“…To overcome this challenge, Desai et al developed an algorithm (using ICD-9 codes, exclusion criteria, and manual review of chemotherapy billing data) to assemble a high-risk neuroblastoma cohort at a single institution [21]. Similarly, Kavcic et al [22] confirmed an algorithm to identify children using PHIS with acute myeloid leukemia (AML) based on ICD-9 diagnosis and manual review of chemotherapy.…”
Section: Other Administrative Databasesmentioning
confidence: 99%